Bosie : the definitive biography of Lord Alfred Douglas. One of the most maligned men in history. - Croft-Cooke, Rupert (London : Four Square Book, 1965)
Fonds Suzan Daniel (FSD)
Fonds Suzan Daniel (FSD)F/02/016 Archief Roger Vertongen
Engels
Monografie